1989
DOI: 10.2307/3868947
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of DNA Sequences Responsible for Ethylene Regulation of a Bean Chitinase Gene in Transgenic Tobacco

Abstract: Expression of at least two genes from bean encoding the defense-related protein chitinase has been shown previously to be transcriptionally regulated by the phytohormone ethylene. We have determined the complete nucleotide sequence of one of these genes, the CH5B gene, which resides on a 4.7-kilobase fragment of bean genomic DNA. The structural gene consists of a single open reading frame and encodes the 301 amino acids of the mature protein and a 26-amino acid signal peptide. The CH5B gene has been introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…Studies of this type with a bean chitinase gene are already in progress [4] and it will be of interest to compare the 5' regulatory regions of the co-induced 1,3-fl-D-glucanase and chitinase genes. The work on bean chitinase genes has been performed in cultivar Saxa [4], which we have now shown to contain a single 1,3-fl-D-glucanase gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of this type with a bean chitinase gene are already in progress [4] and it will be of interest to compare the 5' regulatory regions of the co-induced 1,3-fl-D-glucanase and chitinase genes. The work on bean chitinase genes has been performed in cultivar Saxa [4], which we have now shown to contain a single 1,3-fl-D-glucanase gene.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of this type with a bean chitinase gene are already in progress [4] and it will be of interest to compare the 5' regulatory regions of the co-induced 1,3-fl-D-glucanase and chitinase genes. The work on bean chitinase genes has been performed in cultivar Saxa [4], which we have now shown to contain a single 1,3-fl-D-glucanase gene. Furthermore, the apparent up-regulation of elicitorinduced glucanase transcript appearance by cinnamic acid warrants further study, as recent results from our laboratory have demonstrated the presence of specific cis-acfing elements conditioning the responsiveness of a bean chalcone synthase gene promoter to this phenylpropanoid pathway intermediate (A.D. Choudhary, G. Loake, M.J. Harrison, M. Mavandad, C.J.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ethylene on fruit ripening and other developmental processes is due, at least in part, to changes in the transcription ofspecific genes (3)(4)(5). To understand how gene expression is regulated by ethylene during fruit ripening, a number of ethylene-responsive genes have been cloned and studied in this laboratory (6).…”
mentioning
confidence: 99%
“…Interestingly, the sequence between -7 1 4 and -5 6 7 is conserved in the corresponding region of the other tobacco basic chitinase gene CHN17. This region contains 12 bp direct repeat sequences including a 6-basepair GC-rich sequence (GCCGCC), which is also present in the 5' flanking regions of the bean [6] and the tomato [9] chitinase genes. In the bean chitinase gene the region containing this GC-rich sequence is responsible for ethylene-regulated expression.…”
mentioning
confidence: 99%